Analisis Daya Terima dan Kadar Albumin Keripik Pangsit Panggang Ikan Gabus (Canna Striata) Sebagai Alternatif Makanan Selingan Pengidap Diabetes Melitus - Salsa Alyanda; Nany Suryani; Norhasanah Norhasanah; Nurul Hekmah (Jurnal Kesehatan Indonesia, 2024)
Diabetes Mellitus (DM) is a metabolic disorder caused by insufficient effective insulin in the body, often accompanied by disruptions in fat and protein metabolism, which can lead to complications such as diabetic ulcers. Albumin intake is essential as it plays a key role in maintaining the oncotic pressure of blood plasma. Snakehead fish (Channa striata) is a freshwater species known for its high albumin content, approximately 62.24 g/kg (6.22%). This study aimed to test the albumin levels in roasted snakehead fish dumpling chips with varying formulations (P0 = 0%, P1 = 15%, P2 = 25%, and P3 = 35%) using the Biuret-spectrophotometer method. Additionally, a consumer acceptance test was conducted to evaluate preferences based on color, texture, aroma, and taste through a sensory preference assessment. The results showed that roasted snakehead fish dumpling chips with the P1 formulation were most preferred for color (score: 3.1), while aroma was favored in P0 and P3 (score: 3.0). Taste received similar preference scores across P1, P2, and P3 (score: 3.0), and texture was most preferred in P1 (score: 3.4). The average albumin content in the roasted dumpling chips was as follows: P0 (0.681 g), P1 (0.684 g), P2 (0.729 g), and P3 (0.736 g). Statistical analysis revealed significant differences in consumer acceptance for aroma (p = 0.006) and texture (p = 0.000). Moreover, the addition of snakehead fish significantly increased albumin levels in the chips (p = 0.015). Based on the De Garmo test, the best treatment was identified in P3, with a score of 0.25.